A meteorological study of the high sulphate and nitrate wet deposition episodes in Ontario - "Srivastava, B"; "Yap, D"; "Reid, N W" (1992)
A cooperative study was undertaken to investigate the high wet deposition sulfate and nitrate episodes that contributed to the top 25% of annual deposition in 1985-86 in Ontario. The goals of the study were to determine the meteorological conditions and to analyze the source-receptor relationship of the high deposition episodes. Two stations in the Canadian Air and Precipitation Monitoring Network and two stations in the Acidic Precipitation in Ontario Study were selected in south and central Ontario. A total of 64 episodes, 31 in 1985 and 33 in 1986, were analyzed to determine the meteorological conditions that yielded different types of precipitation and 72-h backward trajectories for 1000, 925, 850, and 700 millibars were computed from a 3-dimensional trajectory model. Narratives and trajectory data for the 31 episodes from 1985 are detailed in this volume. 281 figs.
Keywords: "54 ENVIRONMENTAL SCIENCES"; "ONTARIO"; "ACID RAIN"; "LONG-RANGE TRANSPORT"; "NITRATES"; "NUMERICAL DATA"; "SULFATES"; "ATMOSPHERIC PRECIPITATIONS"; "CANADA"; "DATA"; "DEVELOPED COUNTRIES"; "ENVIRONMENTAL TRANSPORT"; "INFORMATION"; "MASS TRANSFER"; "NITROGEN COMPOUNDS"; "NORTH AMERICA"; "OXYGEN COMPOUNDS"; "RAIN"; "SULFUR COMPOUNDS"; "540120* - Environment, Atmospheric- Chemicals Monitoring & Transport- (1990-)"